Chromosome conformation maps in fission yeast reveal cell cycle dependent sub nuclear structure - Grand RS; Pichugina T; Gehlen LR; Jones MB; Tsai P; Allison JR; Martienssen R; O'Sullivan JM (Oxford University Press)
Successful progression through the cell cycle requires spatial and temporal regulation of gene transcript levels and the number, positions and condensation levels of chromosomes. Here we present a high resolution survey of genome interactions in Schizosaccharomyces pombe using synchronized cells to investigate cell cycle dependent changes in genome organization and transcription. Cell cycle dependent interactions were captured between and within S. pombe chromosomes. Known features of genome organization (e.g. the clustering of telomeres and retrotransposon long terminal repeats (LTRs)) were observed throughout the cell cycle. There were clear correlations between transcript levels and chromosomal interactions between genes, consistent with a role for interactions in transcriptional regulation at specific stages of the cell cycle. In silico reconstructions of the chromosome organization within the S. pombe nuclei were made by polymer modeling. These models suggest that groups of genes with high and low, or differentially regulated transcript levels have preferred positions within the S. pombe nucleus. We conclude that the S. pombe nucleus is spatially divided into functional sub-nuclear domains that correlate with gene activity. The observation that chromosomal interactions are maintained even when chromosomes are fully condensed in M phase implicates genome organization in epigenetic inheritance and bookmarking.
C The Author(s) 2014. Published by Oxford University Press on behalf of Nucleic Acids Research. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http: // creativecommons.org / licenses / by / 4.0 / ), which permits unrestricted reuse, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Science & Technology; Life Sciences & Biomedicine; Biochemistry & Molecular Biology; POL III GENES; SCHIZOSACCHAROMYCES-POMBE; GENOME ORGANIZATION; TRANSCRIPTIONAL MEMORY; METAPHASE CHROMOSOMES; REPLICATION; CHROMATIN; BOOKMARKING; RETROTRANSPOSONS; REORGANIZATION; 05 Environmental Sciences; 06 Biological Sciences; 08 Information and Computing Sciences